Social and Economic Efficiency of Academic Technoparks in Ukraine - Mazur, A.A.; Pustovoit, S.V. (Science and Innovation, 2024)
The socio-economic performance of technology parks established within the framework of the NAS of Ukraine in 2000-2014 has been analyzed. The prospects and expediency of their operation in the next decade have been discussed.